GAMBARAN PENGETAHUAN PASIEN TONSILITIS KRONIS TENTANG TONSILITIS KRONIS DIPOLI THT-KL RUMAH SAKIT UMUM MEURAXA - Eri Ananda; Teuku Aditya Kemal (Jurnal Sains Riset, 2021)
Chronic tonsillitis is the most common disease among throats disease specially in children. Chronic tonsillitis happened because of recurrent inflammation in tonsil that caused by bacteria or virus. Inflammation chronic in the adenoids (tonsila nasofaringea) and tonsils palatina are still a problem the world health. Tarasov and Morozov do a health check on children and adults, the total disease ENT of 190-230/1000 the population, and 38, 4 % of them suffer from tonsillitis chronic.The purpose of this study was to identify patients on chronic tonsilitis in ENT-KL National Hospital Meuraxa Year 2017. This is study is descriptive with cross sectional study at Meuraxa General Hospital. The population in this study were patients with chronic tonsilitis. The number of patients with chronic tonsilitis as much 120 people. The sample taken using accidental sampling by the number of respondents received 10 of the respondents. The result of the study conducted on 10 respondents, there are 7 respondents (70%) to have a good knowledge of tonsillitis chronic, while 3 respondents (30%) have had bad. The conclusion of this study were patients ' knowledge about tonsillitis chronic the majority of good.Keyword : Chronic Tonsilitis, Patient’s Knowladge